The Variable Genomic NK Cell Receptor Locus Is a Key Determinant of CD4+ T Cell Responses During Viral Infection - Raynor, Jana; Lin, Adora; Hummel, Sarah A.; Lampe, Kristin; Jordan, Michael; Hoebe, Kasper; Hildeman, David A. (Frontiers in Immunology, 2020)
Increasing evidence points to a key role for NK cells in controlling adaptive immune responses. In studies examining the role of CD1d on CD4+ T cell responses, we found that a line of CD1d-deficient mice on the C57BL/6J background had a homozygous 129 locus on chromosome 6 containing the entire NK cell gene cluster. Mice possessing this locus (C57BL/6.NKC129) displayed a >10-fold reduction in antigen-specific CD4+ T cell responses after intracranial infection with lymphocytic choriomeningitis virus (LCMV). Neither parental strain displayed defects in viral-specific CD4+ T cell responses. Interestingly, following infection, increased numbers of NK cells accumulated in the lymph nodes of C57BL/6.NKC129 mice and displayed enhanced in vivo functionality. Moreover, depletion of NK cells with anti-asialo-GM-1 antibody in C57BL/6.NKC129 mice resulted in a >20-fold increase in viral-specific CD4+ T cell responses. Mechanistically, we found that dendritic cell antigen presentation and early type I IFN production were significantly decreased in C57BL/6.NKC129 mice, but were restored in perforin-deficient C57BL/6.NKC129 mice or following NK depletion. Together, these data reveal that the variable genomic regions containing the activating/inhibitory NK cell receptors are key determinants of antigen-specific CD4+ T cell responses, controlling type I IFN production and the antigen-presenting capacity of dendritic cells.